2018
DOI: 10.3892/mmr.2018.8533
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1 promotes metastasis in colorectal cancer by regulating the WNT/PCP pathway

Abstract: Colorectal cancer (CRC) is the third leading cause of cancer-associated mortality, and is a major health problem. Collagen type I α 1 (COL1A1) is a major component of collagen type I. Recently, it was reported to be overexpressed in a variety of tumor tissues and cells. However, the function of COL1A1 in CRC remains unclear. Herein, the present study demonstrated that COL1A1 was upregulated in CRC tissues and the paired lymph node tissues. Transwell assays showed that COL1A1 promoted CRC cell migration in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 27 publications
(19 reference statements)
4
107
0
Order By: Relevance
“…In the EC ceRNA network, sponging of overexpressed lncRNA AC009093.1 and under expressed lncRNA MAGI2-AS3, relieved their targets COL1A1 and COL5A2 from being suppressed by hsa-mir-143. Previous studies have suggested that hsa-mir-143 functions as a tumor suppressor in several cancer types [36,37], and COL1A1 has been shown to act as an oncogene to regulate tumors [38][39][40]. Our ndings implied that hsa-mir-143 may function as a tumor suppressor by targeting COL1A1 and COL5A2 in EC and competing with lncRNA MAGI2-AS3/AC009093.1.…”
Section: Discussionsupporting
confidence: 50%
“…In the EC ceRNA network, sponging of overexpressed lncRNA AC009093.1 and under expressed lncRNA MAGI2-AS3, relieved their targets COL1A1 and COL5A2 from being suppressed by hsa-mir-143. Previous studies have suggested that hsa-mir-143 functions as a tumor suppressor in several cancer types [36,37], and COL1A1 has been shown to act as an oncogene to regulate tumors [38][39][40]. Our ndings implied that hsa-mir-143 may function as a tumor suppressor by targeting COL1A1 and COL5A2 in EC and competing with lncRNA MAGI2-AS3/AC009093.1.…”
Section: Discussionsupporting
confidence: 50%
“…6a and Supplementary Fig. 9A) [43][44][45] . The transcriptional activation of these genes is highly dependent on SWINGN expression, as we demonstrated by upregulating its levels by CRISPR activation (CRISPRa) in H226 lung cancer cells.…”
Section: Swingn-mediated Control Of Gas6 Has Implications In Cancermentioning
confidence: 99%
“…In the EC ceRNA network, sponging of overexpressed lncRNA AC009093.1 and under expressed lncRNA MAGI2-AS3, relieved their targets COL1A1 and COL5A2 from being suppressed by hsa-mir-143. Previous studies have suggested that hsa-mir-143 functions as a tumor suppressor in several cancer types [36,37], and COL1A1 has been shown to act as an oncogene to regulate tumors [38][39][40].…”
Section: Discussionmentioning
confidence: 99%